"I'm complicit and I'm ambivalent and that's crazy": Care-less spaces for women in the academy. (March 2017) - Rogers, Chrissie
Abstract: This paper is about three working class women academics in their 40s, who are at different phases in their career. I take a reflexive, feminist, (Reay 2000, 2004, Ribbens and Edwards, 1998) life story approach (Plummer, 2001) in order to understand their particular narratives about identity, complicity, relationships and discomfort within the academy, and then how they inhabit care-less spaces. However unique their narratives, I am able to explore an aspect of higher education – women and their working relationships – through a lens of care-less spaces, and argue that care-less-ness in the academy, can create and reproduce animosity and collusion. Notably, this is damaging for intellectual pursuits, knowledge production and markedly, the identity of woman academics. In introducing this work, I first contextualise women in the academy and define the term care-less spaces, then move onto discuss feminist methods. I then explore and critique in some detail, the substantive findings under the headings of 'complicity and faking it' and 'publishing and collaboration'. The final section concludes the paper by drawing on Herring's (2013) legal premise, in the context of care ethics, as a way to interrogate particular care-less spaces within higher education.